The plastoquinone pool outside the thylakoid membrane serves in plant photoprotection as a reservoir of singlet oxygen scavengers - Ksas, Brigitte; Légeret, Bertrand; Ferretti, Ursula; Chevalier, Anne; Pospíšil, Pavel; Alric, Jean; Havaux, Michel (Plant, cell and environment, 2018)
The Arabidopsis vte1 mutant is devoid of tocopherol and plastochromanol (PC-8). When exposed to excess light energy, vte1 produced more singlet oxygen (1 O2 ) and suffered from extensive oxidative damage compared with the wild type. Here, we show that overexpressing the solanesyl diphosphate synthase 1 (SPS1) gene in vte1 induced a marked accumulation of total plastoquinone (PQ-9) and rendered the vte1 SPS1oex plants tolerant to photooxidative stress, indicating that PQ-9 can replace tocopherol and PC-8 in photoprotection. High total PQ-9 levels were associated with a noticeable decrease in 1 O2 production and higher levels of Hydroxyplastoquinone (PQ-C), a 1 O2 -specific PQ-9 oxidation product. The extra PQ-9 molecules in the vte1 SPS1oex plants were stored in the plastoglobules and the chloroplast envelopes, rather than in the thylakoid membranes, whereas PQ-C was found almost exclusively in the thylakoid membranes. Upon exposure of wild-type plants to high light, the thylakoid PQ-9 pool decreased, whereas the extrathylakoid pool remained unchanged. In vte1 and vte1 SPS1oex plants, the PQ-9 losses in high light were strongly amplified, affecting also the extrathylakoid pool, and PQ-C was found in high amounts in the thylakoids. We conclude that the thylakoid PQ-9 pool acts as a 1 O2 scavenger and is replenished from the extrathylakoid stock.
Keywords: Free Radical Scavengers; Arabidopsis Proteins; oxidační stres; Thylakoids; Oxidative Stress; vysokoúčinná kapalinová chromatografie; Plastoquinone; alkyltransferasy a aryltransferasy; Chloroplasts; tylakoidy; Singlet Oxygen; proteiny huseníčku; chlorofyl; peroxidace lipidů; Electron Spin Resonance Spectroscopy; Light; Alkyl and Aryl Transferases; Chromatography, High Pressure Liquid; Lipid Peroxidation; chloroplasty; scavengery volných radikálů; plastochinon; elektronová paramagnetická rezonance; světlo; singletový kyslík; Chlorophyll